Household Food Dynamics and Food System Resilience Amid the COVID-19 Pandemic: A Cross-National Comparison of China and the United States - Dou, Zhengxia; Stefanovski, Darko; Galligan, David; Lindem, Margaret; Rozin, Paul; Chen, Ting; Chao, Ariana M. (Frontiers in Sustainable Food Systems, 2021)
This cross-national survey-based study examined in real time how the COVID-19 pandemic impacted food-centric matters in 1,732 Chinese and 1,547 U.S. households during the stay-at-home directives. Both cohorts reported increased efficiency in use of food, families spending more time cooking and eating together, and more prudent use of food with less waste. Food purchasing patterns shifted from frequent trips to the store to dramatic increases in online ordering. A small proportion (11% Chinese, 2% U.S. respondents) reported clinically significant weight gains of >4.5 kg. Household food insecurity worsened, with large increases in people worrying about or experiencing food shortage. Collective grocery-shopping experience by survey respondents indicated that the functional stability of food supply systems remained steady. All food types were somewhat available, except for noticeably higher prices widely reported by the Chinese cohort. This study offers insights into future food patterns and sheds light on long-term questions for additional research about how people make decisions and food behavioral changes at times of crisis and the consequences thereafter.